2018
DOI: 10.1111/pan.13414
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anesthesia in endoscopic strip craniectomy: A review of 121 patients

Abstract: SummaryObjective: The aim of this study was to evaluate pre-, intra-, and postoperative anesthetic parameters in endoscopic strip craniectomy in order to improve anesthesiological care. Materials and Methods:This is a retrospective patient cohort study of our first 121 patients treated by endoscopic strip craniectomy. Preoperative as well as intra-and postoperative anesthesiological and neurological parameters were analyzed. Furthermore, the need for intensive care unit admission, blood loss, and blood transfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
(45 reference statements)
0
9
0
Order By: Relevance
“…Dural tearing is one of the most common surgical complications in terms of non-syndromal single-suture synostosis according to the current literature [ 4 ]. Such, as well as further perioperative complications, probably might be underrepresented in our sample considering the apparently low complication rate shown.…”
Section: Discussionmentioning
confidence: 99%
“…Dural tearing is one of the most common surgical complications in terms of non-syndromal single-suture synostosis according to the current literature [ 4 ]. Such, as well as further perioperative complications, probably might be underrepresented in our sample considering the apparently low complication rate shown.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the previously defined exclusion criteria, only 16 articles published between 2000 and 2022 were included (Fig. 1 ) [ 2 , 10 , 14 , 27 39 ]. A total of 18 articles were excluded for the following reasons: improper methods (meta-analysis/systematic review, case reports) n = 4, reported no outcomes of interest ( n = 4), no full text was found ( n = 2), non-craniosynostosis patients ( n = 2), and incomplete description of perioperative pain management protocol ( n = 6).…”
Section: Resultsmentioning
confidence: 99%
“…In total, nine articles describing the complete postoperative analgesic protocol were identified [ 2 , 10 , 27 29 , 31 , 33 , 35 , 37 ], including 407 (47.9%) patients. In a prospective randomized controlled trial of 40 craniosynostosis patients, Van der Marel et al compared oral acetaminophen versus rectal acetaminophen.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations